2023
DOI: 10.3390/proteomes11010001
|View full text |Cite
|
Sign up to set email alerts
|

The Need for Biomarkers in the ALS–FTD Spectrum: A Clinical Point of View on the Role of Proteomics

Abstract: Frontotemporal dementia (FTD) and amyotrophic lateral sclerosis (ALS) are severely debilitating and progressive neurodegenerative disorders. A distinctive pathological feature of several neurodegenerative diseases, including ALS and FTD, is the deposition of aberrant protein inclusions in neuronal cells, which leads to cellular dysfunction and neuronal damage and loss. Despite this, to date, the biological process behind developing these protein inclusions must be better clarified, making the development of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 131 publications
0
11
0
1
Order By: Relevance
“…The last two decades of research have pushed the identification and monitoring of fluid and imaging biomarkers, aiming at revealing pathogenic mechanisms and potential therapeutic targets [ 4 ]. Since ALS and other NDDs share the deposition of misfolded proteins as a common pathogenic mechanism, a promising field of research is represented by the investigation of protein complexes and their interactions, but large-scale confirmation is still needed [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The last two decades of research have pushed the identification and monitoring of fluid and imaging biomarkers, aiming at revealing pathogenic mechanisms and potential therapeutic targets [ 4 ]. Since ALS and other NDDs share the deposition of misfolded proteins as a common pathogenic mechanism, a promising field of research is represented by the investigation of protein complexes and their interactions, but large-scale confirmation is still needed [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, proteomics gives a lower identification rate (<10% of total proteins) but provides direct information on possible drug targets. Thus, proteomics is a good choice for biomarker research [ 141 ]. One study from Xu et al demonstrated that the plasma proteomic profile of ALS correlates with some clinical features [ 43 ].…”
Section: Molecular Heterogeneitymentioning
confidence: 99%
“…Given that synaptic dysfunction often precedes neuronal loss, the presence of altered synaptic biomarkers could signal disease onset before the appearance of clinical symptoms. Additionally, biomarkers like NfL that correlate with disease progression could provide valuable prognostic information, guiding patient care and management (Swift et al, 2021;Vignaroli et al, 2023).…”
Section: Opportunities For Synaptic Biomarkers In Als and Ftdmentioning
confidence: 99%